Detection for The Production of Siderophore in Burkholderia cepacia Isolated From the Rhizosphers of Some Plants and studing the Effect of the Bacterial Filtrate and Extract on Some Pathogenic Fungi - Mussa, A. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
bstract This study was performed to isolate and identify the Burkholderia cepacia from rhizosphers of different plants and study their ability to produce Siderophore, the study was also aimed to assess the antifungal activity of the bacterial filtrate and extracts of the isolates against some pathogenic fungi. The isolate which showed higher inhibitory effects was selected for extraction of some active metabolites produced by it, and evaluate the activity in vitro, via inhibition of the growth of the fungi using different concentrations of extract (50, 100, 200 )µL/ml , The results showed that out of (250) samples of soil , (8) isolates (3.2%) gave positive results for Burkholderia cepacia ,all the isolates have the ability to produce Siderophore .the filtrate and extract of B.cepacia that contain the active metabolites showed higher inhibition effect against number of pathogenic fungi which include : (Tricophyton sp, Alternaria sp ,Aspergillus flavus ,Fusarium sp ,Candida albicans , Cryptococcus neoformans) The inhibition percentage of filtrate was( 20 – 60)% against Tricophyton sp , Alternaria sp ,Aspergellus flavus ,Fusarium sp , and the extract showed higher inhibition effect, the concentrate 200µL/ml was the beast by obtained inhibition percentage 100% against Trichophyton sp, Alternaria sp.While against Candida albicans, Cryptococcus neoformans the inhibition zone of filtrate was (8-15) mm, and the inhibition zone of extract was (20)mm